2017
DOI: 10.1080/13548506.2017.1363396
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perceived effort–reward imbalance on workplace bullying: also a matter of organizational identification

Abstract: Work environments characterized by inadequate work conditions have been widely recognized as being particularly prone to the occurrence and exacerbation of bullying behavior. Accordingly, this longitudinal study aimed to explore whether the impact of effort-reward imbalance (ERI) on workplace bullying was mediated by a lower perception of organizational justice, and whether the association between ERI and perceptions of justice was moderated by organizational identification. In the current study, a sample of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…Experiences of injustice have also been reported to be a severe stressor in the workplace (Greenberg, 2006). In line with the idea that work-related stress may induce bullying and that perceptions of injustice are a central stressor, the present study aligns with Guglielmi et al (2018) to investigate whether the Effort-Reward Imbalance (ERI) Model (Siegrist, 1996), is valuable in understanding reports of exposure to WB.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Experiences of injustice have also been reported to be a severe stressor in the workplace (Greenberg, 2006). In line with the idea that work-related stress may induce bullying and that perceptions of injustice are a central stressor, the present study aligns with Guglielmi et al (2018) to investigate whether the Effort-Reward Imbalance (ERI) Model (Siegrist, 1996), is valuable in understanding reports of exposure to WB.…”
Section: Introductionmentioning
confidence: 84%
“…Our study aimed to advance insights into the work environment hypothesis by investigating the role of a well-established theoretical stress framework (ERI), so far only investigated once in bullying research (Guglielmi et al, 2018). Our research advanced research by employing a large sample of employees, employed in 19 organizations across different sectors.…”
Section: Discussionmentioning
confidence: 99%
“…A further implication entails the promotion of an approach that leads to experience one's job as more engaging and meaningful (i.e., job crafting strategies). As a result, workers can proactively tackle their job demands, prevent the occurrence of counterproductive work behavior and perceive higher levels of well-being (Ingusci et al, 2016;Guglielmi et al, 2017). Previous findings among nurses' managers revealed that hardiness training could boost workers' confidence in their ability to influence the course of events and to translate demanding situations into learning opportunities (Judkins et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We must consider also the practical intervention strategies that could be implemented to tackle the main threats to correctional workers’ well-being. For example, strategies designed to enhance the perception of managerial support and organizational justice should be further developed in correctional settings, as these strategies may significantly prevent the occurrence of counterproductive work behavior associated with employees’ mental health symptoms, such as presenteeism and workplace bullying ( Guglielmi et al, 2018 ; Mazzetti et al, 2019 ). Additionally, respondents’ concerns included insufficient benefits and wages, a need to recognize mental health, and how the interacting challenges impact mental health treatment-seeking, all of which provide avenues for future research and policy development.…”
Section: Conclusion and Future Research Needsmentioning
confidence: 99%